Evaluation of therapeutic efficacy, safety and economy of ERCP and LTCBDE in the treatment of common bile duct stones - Zhang, Renjie; Liu, Jialin; Li, Huizhen; Zeng, Qingteng; Wu, Shenfeng; Tian, Hengyu (Frontiers in Physiology, 2022)
Objectives This study further compared the endoscopic retrograde cholangiopancreatography (ERCP) and laparoscopic transcystic common bile duct exploration (LTCBDE) approaches in the treatment of common bile duct stones (CBDS) from the perspective of efficacy, safety and economy. Methods The therapeutic efficacy and safety of ERCP and LTCBDE approaches were retrospectively compared. Cost-effectiveness analysis of clinical economics was performed to analyze and evaluate the two approaches. Results There was no significant difference in the success rate of surgery and bile stone residue between ERCP and LTCBDE group. The incidence of postoperative complications in ERCP group was significantly higher than that in the LTCBDE group; while the incidence of pancreatitis in the ERCP group was significantly higher than that in the LTCBDE group. There was no significant difference in biliary infection, bile leakage and sepsis between ERCP and LTCBDE groups. In terms of cost, the costs of surgery and nursing were significantly lower, the costs of treatment and sanitary materials were significantly higher in the ERCP group than that in the LTCBDE group. There was no significant difference in the costs of medical examination, laboratory test, medicine cost and total cost between ERCP group and LTCBDE group. The total length of hospital stay, length of hospital stay before surgery and duration of surgery in the ERCP group were significantly lower than that in the LTCBDE group; there was no significant difference in length of hospital stay after surgery between the ERCP and LTCBDE group. The cost-effectiveness ratio of ERCP group was 34171.25, and the cost-effectiveness of LTCBDE group was 34524.25. The incremental cost-effectiveness ratio (ICER) of the two groups was 51415. Conclusions ERCP and LTCBDE approaches had similar therapeutic efficacy in the treatment of CBDS. The safety of LTCBDE approach is superior to that of ERCP approach for the treatment of CBDS. ERCP approach is more economical in the treatment of CBDS than LTCBDE approach.